Sosialisasi Pencegahan Covid 19 bagi Anak di PAUD Mutiara Islami Melalui Media Online - Jessica Festy Maharani; Ni Made Sulastri; Herlina Herlina; Dewi Rayani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of this service activity is to provide an understanding of Covid 19 and how to deal with fear and anxiety in children and parents. The method of implementing the activity uses online media, which is followed by teachers and parents, as well as the presentation of interesting applications for PAUD Mutiara Islam Mataram. The result of activity is the existence of useful knowledge on how to deal with anxiety and prevent the Covid-19 outbreak. Active discussion and enthusiastic participants when receiving the material presented by the speaker.